Individualized Pterional Keyhole Clipping Surgery based on a Preoperative Three-Dimensional Virtual Osteotomy Technique for Unruptured Middle Cerebral Artery Aneurysm - Mori, K.; Esaki, T.; Yamamoto, T.; Nakao, Y. (min - Minimally Invasive Neurosurgery, 2011)
Individualized surgical simulation using three-dimensional (3D) imaging to allow safe performance of clipping surgery for unruptured middle cerebral artery (MCA) aneurysm via pterional keyhole mini-craniotomy was performed in 100 consecutive patients.3D images were reconstructed of the skin, skull, cerebral arteries and veins, and aneurysm. The size, shape, and location of the scheduled keyhole and the patient’s head position were individually optimized using this preoperative simulation system. The site of opening of the sylvian fissure was also preoperatively determined according to the spatial relationships between the aneurysm and sylvian veins. 110 pterional keyhole clipping surgeries were consecutively performed in 100 patients.The mean diameter of the pterional keyhole was 25±2 mm. Magnetic resonance imaging detected lacunar infarction in 4 cases (3.6%) but no other abnormalities. 1 patient suffered a reversible ischemic neurological deficit and 1 patient (79 years old) showed mild dementia. The modified Rankin scale at 3 months after the operation was grade 0 in all cases except 1 patient with mild dementia (grade 1). Mini-mental state examination, Hamilton rating scale for depression, and Beck depression inventory were all significantly improved (p<0.01) after the operations.Pterional keyhole clipping surgery based on careful surgical simulation with 3D images is a safe and less invasive means to treat relatively small unruptured MCA aneurysms.
Keywords: keyhole surgery; pterional keyhole; middle cerebral artery; cerebral aneurysm